LEGAL STATUS OF COOPERATIVE MEMBERS - Vardanyan, Artur (State and Law, 2021)
The article analyzes the legal status of the cooperative member. All the essential rights and duties of the member were mentioned, the international practice on member status were studied in Russian Federation, in different countries of EU and also in United States. A number of offers were made for defining rights and obligations of the member, and for regulation of labour relations between member and cooperative.
Keywords: cooperative; cooperative member; legal statof cooperative member; labor rights of a member